2000
DOI: 10.1063/1.371852
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rapid thermal annealing on the optical properties of GaNxAs1−x/GaAs single quantum well structure grown by molecular beam epitaxy

Abstract: The effect of rapid thermal annealing (RTA) on the optical properties of GaNxAs1−x/GaAs strained single quantum well (SQW) was studied by low-temperature photoluminescence (PL). The GaNxAs1−x/GaAs SQW structures were prepared by dc active nitrogen plasma assisted molecular beam epitaxy. PL measurements on a series of samples with different well widths and nitrogen compositions were used to evaluate the effects of RTA. The annealing temperature and time were varied from 650 to 850 °C and 30 s to 15 min, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(14 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…As a result, it is important to note that the PL spectra exhibit the characteristics of a near band edge excitonic emission [11,13]. This emission showed a substantial blue shift with the longer annealing time, and the long wavelength emission at about 1.3 mm (0.95 eV) was recorded at 10 K. In general meaning, the blue shift has been attributed mainly to the following possible reasons: (i) the N out-diffusion [5] and (ii) the improvement of alloy uniformity resulting in the decrease of the value of the localization potential [14]. In order to qualitatively describe the evolution of the blue shifts, we have taken the (0 0 4) HRXRD 2y/o profiles, the (1 1 5) reciprocal space mapping, and the Raman spectra of the GaAsN layers before and after annealing.…”
Section: Article In Pressmentioning
confidence: 97%
See 1 more Smart Citation
“…As a result, it is important to note that the PL spectra exhibit the characteristics of a near band edge excitonic emission [11,13]. This emission showed a substantial blue shift with the longer annealing time, and the long wavelength emission at about 1.3 mm (0.95 eV) was recorded at 10 K. In general meaning, the blue shift has been attributed mainly to the following possible reasons: (i) the N out-diffusion [5] and (ii) the improvement of alloy uniformity resulting in the decrease of the value of the localization potential [14]. In order to qualitatively describe the evolution of the blue shifts, we have taken the (0 0 4) HRXRD 2y/o profiles, the (1 1 5) reciprocal space mapping, and the Raman spectra of the GaAsN layers before and after annealing.…”
Section: Article In Pressmentioning
confidence: 97%
“…Low-bandgap Ga(In)AsN-based heterostructures are expected as useful for optoelectronic devices such as laser diodes emitting at 1.3 and 1.55 mm for optical communication systems [1][2][3]. The GaAsN films with N contents up to 5-8% were grown on a GaAs(0 0 1) substrate by metalorganic vapor phase epitaxy (MOVPE) [4][5][6]. However, the optical quality of GaAsN has been found to degrade with higher N incorporation.…”
Section: Introductionmentioning
confidence: 99%
“…Two possible explanations have, so far, been proposed to account for the observed blue shift of GaNAs PL spectra with annealing. Li et al Li et al (2000) observed a RTA-induced blue shift in the low temperature photoluminescence (LTPL) spectrum of a single GaNAs quantum well and explained it quantitatively by nitrogen diffusion out of the quantum well. On the other hand, Buyanova et al performed low temperature optical studies of both GaNAs multi-quantum wells and thick epilayers and showed that annealing could induce a blue shift of the PL spectra without necessarily changing the photoluminescence excitation (PLE) spectra energy, that is, the peak PL emission wavelength.…”
Section: Barriersmentioning
confidence: 99%
“…The emission wavelength of such GaInNAs layers was strongly blue-shifted when, after the growth of the actual GaInNAs layer, the growth temperature was raised for growing AlGaAs-based top layers (such as distributed Bragg reflectors in vertical-cavity surface-emitting laser (VCSEL) structures or for confinement and guiding in edge emitting laser structures). This led to a number of annealing studies which yield somewhat contradictory results Bhat et al (1998) ;Francoeur et al (1998); Gilet et al (1999); Kitatani et al (2000); Klar et al (2001); Li et al (2000); Pan et al (2000); Polimeni et al (2001); Rao et al (1998); Spruytte et al (2001a);v H G Baldassarri et al (2001); Xin et al (1999). This, ofcourse, is partly due to the different annealing conditions and growth conditions used, but is also a strong manifestation of the metastability of this alloy system.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with work by others that focused on GaN x As 1Ϫx /GaAs quantum wells. 21 Therefore, we believe that thermal annealing primarily leads to the recovery of the plasma-related crystal damage caused by the N incorporation.…”
Section: Section Iv: 32% In-containing Quantum Wells With Barriers Comentioning
confidence: 99%